Keberadaan Lesbian di Kota Syariat: Faktor dan Interaksi Subjek - Kasmaya Kasmaya (Jurnal Sosiologi Agama Indonesia (JSAI), 2021)
This study aims to describe the way lesbians interact with the environment where the majority of them are Muslims and the factors that influence a person to become a lesbian. The method used is a qualitative method with a case study approach. The informants of this study were four lesbians who lived in the city of Banda Aceh. The results of this study indicate that there are several things that underlie social interactions that shape lesbian behavior in an environment where the majority of Muslims are Muslims, that is family factors, fun, and trauma. The way lesbians adapt and run a partner relationship is the same as for heterosexual couples in general. However, for a more intimate relationship, this lesbian couple avoids their daily activities, then changes their appearance like men so that people don't suspect them.